Developing Smart Tourism Tools and Platforms: from the RESETTING experience to AI-based futures - Brito e Abreu, F. (10th International Conference on Digital Arts, Media and Technology (DAMT) and 8th ECTI Northern Section Conference on Electrical, Electronics, Computer and Telecommunications Engineering (NCON), 2025)
This talk will describe the challenges and breakthroughs in developing several smart tourism tools and platforms to address critical issues such as overcrowding, resource management, and destination sustainability as part of the RESETTING project funded by the European Commission. Using cutting-edge open-source technologies, the project provided actionable insights to tourism stakeholders, especially SMEs, to improve the visitor experience while preserving destinations' cultural and environmental integrity. One of the key innovations developed within RESETTING was a distributed IoT-based crowd monitoring system that provides real-time data based on the detection of mobile phones in the vicinity of hot tourist attractions, enabling local authorities and tourism managers to take timely action to prevent overcrowding, balance the needs of residents and visitors, preserve the attractiveness of the destination, and reduce the environmental footprint. To consider the topology of destinations, we have developed the Carrying Capacity Calculator. This interactive web application estimates the optimal number of visitors a destination can accommodate without compromising its cultural, social, and environmental assets. These estimates can be calibrated by considering factors such as local infrastructure, natural resources, and visitor behavior. The next step was a geo-temporal 3D crowd visualization platform that combined the data provided by the previous two tools. An intuitive 3D interface improves understanding of crowd movement and density in both spatial and temporal dimensions, allowing destination managers to identify peak times and locations that require proactive management. We can also provide predictions using AI-based techniques. This platform can be used with other sources of crowd detection beyond our Wi-Fi sensors, such as mobile network data and motion detectors, as we have done in Lisbon and Melbourne. Last, we have laid the foundation for the European Smart Tourism Observatory, an online platform that aggregates data from different sources, namely available smart tourism tools and initiatives across Europe. This Observatory can provide valuable insights for policymakers, researchers, and tourism professionals across Europe, supporting the industry's transition towards more resilient and sustainable tourism models by delivering a geo-referenced and content-rich awareness of their existence. Finally, this talk will provide details on ongoing and future developments to extend and further refine these smart tourism tools and platforms by leveraging recent AI breakthroughs. Stakeholders from the tourism sector will be invited to collaborate in these efforts, building on RESETTING's experience in promoting innovation and sustainability in tourism management.